Implementation of Patient Fall Risk Assessment by Nurses at Pamela Tebing Tinggi Hospital in 2023 - Bambang Sumantri (Medistra Medical Journal (MMJ), 2025)
This study aims to analyze the implementation of the risk assessment of patients falling by nurses at Sri Pamela Tebing Tinggi Hospital in 2023. The method used is an analytical descriptive approach with a cross-sectional design. The study population involved all nurses on duty in the inpatient room, with samples taken by purposive sampling. Data were collected through direct observation of the implementation of fall risk assessments and structured interviews. The results showed that most nurses had carried out a good fall risk assessment, but there were some nurses who had not reassessed low-risk patients with a fall if there was a change in condition. Fall risk prevention measures have also been well implemented, although there are still shortcomings in implementation of high-risk fall prevention measures. It is recommended to hospitals to improve training and supervision for nurses, as well as strengthen the implementation of Standard Operating Procedures (SOPs) related to the assessment and prevention of fall risks.